E. coli and Salmonella on animal farms: sources, survival and management - Max Teplitski (EDIS, 2006)
Significant effort has been made by universities and research agencies to help eliminate Salmonella and pathogenic E. coli from animal and dairy farms. This article highlights findings from these recent studies. This document is SL-239, a fact sheet of the Soil and Water Science Department, UF/IFAS Extension. Original publication date March 2006.